Internal mammary artery smooth muscle cells resist migration and possess high antioxidant capacity - Mahadevan, Vaikom; Campbell, Malcolm; McKeown, Pascal; Bayraktutan, Ulvi (Elsevier, 2006)
Objective- This study investigated whether differences exist in atherogen-induced migratory behaviors and basal antioxidant enzyme capacity of vascular smooth muscle cells (VSMC) from human coronary (CA) and internal mammary (IMA) arteries. Methods- Migration experiments were performed using the Dunn chemotaxis chamber. The prooxidant [NAD(P)H oxidase] and antioxidant [NOS, superoxide dismutase, catalase and glutathione peroxidase] enzyme activities were determined by specific assays. Results- Chemotaxis experiments revealed that while both sets of VSMC migrated towards platelet-derived growth factor-BB (1-50 ng/ml) and angiotensin II (1-50 nM), neither oxidized-LDL (ox-LDL, 25-100 Ã¯ÂÂg/ml) nor native LDL (100 Ã¯ÂÂg/ml) affected chemotaxis in IMA VSMC. However, high dose ox-LDL produced significant chemotaxis in CA VSMC that was inhibited by pravastatin (100 nM), mevastatin (10 nM), losartan (10 nM), enalapril (1 Ã¯ÂÂM), and MnTBAP (a free radical scavenger, 50Ã¯ÂÂ Ã¯ÂÂM). Microinjection experiments with isoprenoids i.e. geranylgeranylpyrophosphate (GGPP) and farnesylpyrophosphate (FPP) showed distinct involvement of small GTPases in atherogen-induced VSMC migration. Significant increases in antioxidant enzyme activities and nitrite production along with marked decreases in NAD(P)H oxidase activity and O2 .- levels were determined in IMA versus CA VSMC. Conclusions- Enhanced intrinsic antioxidant capacity may confer on IMA VSMC resistance to migration against atherogenic agents. Drugs that regulate ox-LDL or angiotensin II levels also exert antimigratory effects.